Shades of complicity: archives of the ‘implicated subject’ - Duncan, Derek (Modern Italy : journal of the Association for the Study of Modern Italy, 2024)
Knowledge of the Arandora Star is no longer limited to members of the UK's historic Italian community but is shared by a much larger constituency thanks to the greater accessibility of historical documents relating to the sinking of the ship, and to the substantial volume of new creative work inspired by it. This article examines this expansion of historical memory by following two discrete but entangled strands. The first follows the construction of the Arandora Star archive, starting from the author's chance personal encounter with a photograph. The second involves a close reading of Francine Stock's A Foreign Country (1999) and Caterina Soffici's Nessuno può fermarmi (2017), two novels that explore how people outside the historic Italian community recognise their implication in the sinking and its aftermath. Both foreground the intergenerational and transnational transmission of difficult memory and the ways in which the Arandora Star functions as an unstable point of historical knowledge and ethical judgement.